2014
DOI: 10.1186/1865-1380-7-18
|View full text |Cite
|
Sign up to set email alerts
|

The emergency to home project: impact of an emergency department care coordinator on hospital admission and emergency department utilization among seniors

Abstract: BackgroundSeniors comprise 14% to 21% of all emergency department (ED) visits, yet are disproportionately larger users of ED and inpatient resources. ED care coordinators (EDCCs) target seniors at risk for functional decline and connect them to home care and other community services in hopes of avoiding hospitalization.The goal of this study was to measure the association between the presence of EDCCs and admission rates for seniors aged ≥ 65. Secondary outcomes included length of stay, recidivism at 30 days, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…A total of 2000 citations were identified from a combined search of databases, reviewing bibliographies of relevant review articles, and targeted searches of http://clinicaltrials.gov and Scopus. After applying eligibility criteria, 17 articles describing 15 studies, nine randomized and six nonrandomized were included (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 2000 citations were identified from a combined search of databases, reviewing bibliographies of relevant review articles, and targeted searches of http://clinicaltrials.gov and Scopus. After applying eligibility criteria, 17 articles describing 15 studies, nine randomized and six nonrandomized were included (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies, two randomized, examined the effect of ED interventions on hospitalization at the index ED visit . Overall, there was no pattern of interventions on hospitalization at the index visit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While we did not compare ED revisits with non-fall patients, our revisit findings are within the wide range of overall older adult ED revisit rates and similar to a recent study reporting a 30-day ED revisit rate among fallers of 13.6%. 18 McCusker's study of patients aged 65 and above who were discharged from the ED found 19.3% of patient made an ED revisit within 30 days and over 40% within 6 months. 19 Friedmann's single site cohort study of elderly patients who were discharged from the ED found a 12% revisit rate at 30 days among older adult ED discharged patients and a 19% ED revisit rate at 90 days.…”
Section: Discussionmentioning
confidence: 99%
“…Although a modest positive effect was shown in reducing unscheduled revisits, again this study population consisted exclusively of patients that were discharged from the ED. In a study by Gagnon et al, nurse case management of elderly patients discharge from the ED resulted in higher rates of ED readmission, with no improvement in other outcomes [16]. In all of these studies, seniors were discharged from the ED on the index visit, and all enrolled patients were community-dwelling and not institutionalized.…”
Section: Discussionmentioning
confidence: 99%